2010
DOI: 10.1021/jp9046903
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mechanisms and Kinetics of Photoinduced Silver Nanoparticles in Mesostructured Hybrid Silica Films under UV and Visible Illumination

Abstract: The growth of silver nanoparticles in mesostructured hybrid silica films under laser illumination is investigated by optical absorption spectroscopy and transmission electron microscopy. At low laser doses in the UV range, a blue-shift of the plasmon resonance is observed for increasing particle size. This size dependence is interpreted on the basis of the Mie theory assuming a two-layer core-shell model resulting from the localization of the nanoparticles in the block copolymer part of the film. At higher las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Its refractive index was deduced from the Maxwell-Garnett theory using for the refractive index of small Ag nanoparticles the expression of the dielectric function of bulk silver, corrected in size taking into account the classical free path effect. 36 The overall TiO 2 thickness was 155 nm. A constant absorption coefficient was also applied to TiO 2 to take into account losses caused by scattering by the nanocrystals.…”
Section: Electromagnetic Modeling Of the Waveguiding Metallic Photoni...mentioning
confidence: 99%
“…Its refractive index was deduced from the Maxwell-Garnett theory using for the refractive index of small Ag nanoparticles the expression of the dielectric function of bulk silver, corrected in size taking into account the classical free path effect. 36 The overall TiO 2 thickness was 155 nm. A constant absorption coefficient was also applied to TiO 2 to take into account losses caused by scattering by the nanocrystals.…”
Section: Electromagnetic Modeling Of the Waveguiding Metallic Photoni...mentioning
confidence: 99%
“…[17] It is, however, interesting to note that although the term 'mechanism' was consistently mentioned in that paper, in kinetic sense a 'mechanism' has to consist of elementary or quasi-elementary steps exclusively, where law of mass action type kinetics is uniquely fulfilled for each and every step. Misuse of term 'mechanism' and 'kinetic model' is not restricted to self-replication studies it may as well be found in other fields [18][19][20] thus the problem seems to be more general than one would otherwise expect. Recently, Virgo et al showed that in case of a polymerization model not only first-order autocatalysis but even more complex overall positive feedback processes may appear resulting in a superexponential growth.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent photoreduction of the coordinated silver cations in 1Ag + LB films results in the formation of disklike metallic silver nanoparticles, which cover a significant portion of the film surface, and this system is denoted here as 1AgNP. The photoreduction mechanism of silver cations 16 as well as the subsequent nucleation and growth mechanism of the silver nanoparticles 17,18 have been studied in detail before. Fig.…”
Section: Introductionmentioning
confidence: 99%